Leaching of Oil from Tuna Fish Liver by Using Solvent of Methyl-Ethyl Ketone - Lubis, Mirna Rahmah; M., Nova (Jurnal Rekayasa Kimia & Lingkungan, 2013)
Research of oil leaching from Tuna Fish Liver has been carried out by extracting of tuna fish liver in soxhlet by using methyl-ethyl ketone as solvent. Liver of fresh tuna fish is blended, put into soxhlet, and extracted at temperatures of 60oC, 65oC, 70oC, 75oC, and 80oC. After obtaining the oil, separation between solvent and oil is carried out by distillation. Oil obtained is analyzed by testing the yield, acid number, Iodine value, viscosity, and its impurities content. Yield obtained is influenced by temperature and time of leaching. Both variables indicates that the higher the variables, the more fish liver oil obtained. Maximum yield obtained is 25.552% at operating condition of leaching temperature 80oC, and leaching duration of 5 hours.